READING INTEREST, READING SELF-EFFICACY, AND READING COMPETENCY IN THE JUNIOR HIGH SCHOOL - Mira, Putu; Tantra, Dewa Komang; Saputra, I Nyoman Pasek Hadi (Universitas Pendidikan Ganesha, 2020)
The research aimed at describing and correlating the students’ reading interest, reading self-efficacy, and their reading competency in Sekolah Menengah Pertama Negeri (SMPN) 3 Singaraja. This research used a quantitative research design. The sample consisted of 102 students in three classes of the eighth-grade students that were chosen by using cluster quota sampling. Three instruments to collect the data such as a reading interest scale, a reading self-efficacy scale, and an objective reading competency test. The data were analyzed descriptively and inferentially. The result revealed that the students’ reading interest, reading self-efficacy, and reading competency on high-order-items are classified into moderate levels. The pair-wise correlation between the students’ reading interest and reading self-efficacy, the students reading interest and reading competency, the students’ reading self-efficacy and reading competency on high-order-items are correlated positively and significantly, as well as the multiple relationships between the three variables.